A practical study of the properties of fabrics produced from two different types of yarn (Damascus University Journal for engineering sciences, 2021)
The properties of the compact yarns are different from the of the properties ring yarn in that as a result of the development that has occurred on  compact spinning machine, the compact yarns have better properties from ring yarn The resulting fabrics with different specifications for specification fabrics produced from threaded ring.Comparatively good knitting performances have shown by the Ring and compact yarns. Tensile, evenness and hairiness of the yarns and bursting strength, abrasion resistance, pilling effect and drapability of the knitted fabrics were studied.
Keywords: Yarns, Knitted Fabrics; Properties; Ring and Compact Yarns